2013
DOI: 10.1007/s10549-013-2674-z
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for shedding of circulating tumor cells to the peripheral venous blood as a result of mammographic breast compression

Abstract: This pilot study aimed to investigate whether mammographic compression procedures might cause shedding of tumor cells into the circulatory system as reflected by circulating tumor cell (CTC) count in peripheral venous blood samples. From March to October 2012, 24 subjects with strong suspicion of breast malignancy were included in the study. Peripheral blood samples were acquired before and after mammography. Enumeration of CTCs in the blood samples was performed using the CellSearch® system. The pressure dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
2
23
2
Order By: Relevance
“…Vertebrae were more likely to form metastases, which demonstrated that different bones possess different microenvironments where CTCs are inclined to settle in. DTCs could still disseminate to other remote organs even the primary tumor has been resected for years 23. Bone metastases can be applied as the prognostic factor to colon cancer with rare occurrence of bone metastases, as well as to breast cancer with frequent occurrence of bone metastases 28.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrae were more likely to form metastases, which demonstrated that different bones possess different microenvironments where CTCs are inclined to settle in. DTCs could still disseminate to other remote organs even the primary tumor has been resected for years 23. Bone metastases can be applied as the prognostic factor to colon cancer with rare occurrence of bone metastases, as well as to breast cancer with frequent occurrence of bone metastases 28.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pilot study by Förnvik et al [27], examining the pressure distributions during mammographic compression of known lesions, found no such evidence. However, over-compression is still a cause of unnecessary pain.…”
Section: Over-compressionmentioning
confidence: 96%
“…Many previous studies 8, 14, 15 used EpCAM-based approaches to quantify the number of tumor cells shed during surgery. While nearly all EpCAM+ cells in the peripheral circulation (circulating tumor cells) are tumor cells 16 , too many normal epithelial cells are dislodged during surgery to render EpCAM an equally good marker for intraoperatively shed tumor cells.…”
Section: Discussionmentioning
confidence: 99%